2022
DOI: 10.3389/fneur.2021.688616
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Proprioceptive Impairment and Motor Deficits After Stroke: A Meta-Analysis Review

Abstract: Introduction: Proprioceptive impairment is a common symptom after stroke. Clarifying how proprioception correlates with motor function after stroke may be helpful in optimizing proprioception-augmented movement training. Previous studies have shown inconsistent findings. A meta-analysis is an optimal method to explore the correlation and identify the factors contributing to these inconsistencies.Objective: To explore the correlation between proprioception and motor function after stroke through a meta-analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
(270 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, WBVE has been shown to improve proprioceptive feedback, which is crucial for maintaining balance and stability during movement [ 60 ]. Enhanced proprioception can lead to improved motor control and reduced risk of falls and injuries, contributing to decreased disability scores [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, WBVE has been shown to improve proprioceptive feedback, which is crucial for maintaining balance and stability during movement [ 60 ]. Enhanced proprioception can lead to improved motor control and reduced risk of falls and injuries, contributing to decreased disability scores [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knee proprioception plays a key role in maintaining the joint stability and coordination during movement [ 30 ]. Due to the occurrence of proprioception deficits in a large group of people after a stroke (approximately 50–60% of stroke survivors) and their association with mobility and balance disorders, our set of tests included the assessment of one of the proprioception components, which is joint position sense [ 31 , 32 , 33 ]. The patients’ task during the JPS test was similar to the studies conducted by Imanawanto et al [ 34 ] and Hwang et al [ 35 ], restoring the position of 30° of knee flexion and then the position of 60° of knee flexion.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not differentiate balance ability measured by using the BBS from functional mobility measured by the walking test, considering that BBS is an instrument used to evaluate functional mobility on sitting, standing, and positional or postural transfer, and it correlates with gait velocity ( 31 ). We categorized outcomes based on the ICF framework, a widely used method in meta-analysis studies, ensuring that more studies are included in subgroup meta-analyses ( 4 , 24 ). Unlike previous reviews, our study discovered that CIMT had superior short-term effects on activity performance, movement function, and participation than the conventional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses were conducted across all studies of the same design first. Only one outcome measure of each study was included in each meta-analysis, which appeared most frequently in included studies of the corresponding meta-analysis ( 24 , 25 ). Considering ICF categories of outcome measures showing significant contributions to the effect sizes found in the present study (reported in the section Results), meta-analyses across studies with the same design but grouped based on ICF categories of outcome measures were further conducted.…”
Section: Methodsmentioning
confidence: 99%